Cymbella xiaojinensis sp. nov., a new cymbelloid diatom species (Bacillariophyceae) from high altitude lakes, China - Zhang, Yun; Liao, Mengna; Li, Yan-Ling; Chang, Feng-Qin; Kociolek, John Patrick (Phytotaxa, 2021)
This paper describes a new species of Cymbella from an alpine lake in the Hengduan Mountains, southwestern China. The detailed morphological description of the new species, named Cymbella xiaojinensis sp. nov. is presented, based on light and scanning electron microscopy. The main features of C. xiaojinensis are characterized by strongly dorsiventral, triangular valves with a strongly reverse-lateral raphe system positioned near the proximal ends and an asymmetrical, larger central area, occupying approximately 1/2 of the width with the valve. Most morphological characteristics of the new species are similar to C. shudunensis, C. terrafuegiana, C. pamirensis, and C. gravida, but differ in details of size, valve shape, striae density, central area, and number of stigmata.